Contribution of TRMM 3B42 Data to Improve Knowledge on Rainfall in the Kayanga/Geba River Basin (Republic of Guinea, Senegal and GuineaBissau) - Sambou, Saly; Dacosta, Honore; Deme, Abdoulaye; Diouf, Ibrahima (European Scientific Journal, ESJ, 2018)
The use of Tropical Rainfall Measuring Mission (TRMM) data is an option for counteracting challenge of the lack of ground based observations, particularly in Kayanga/Gêba. This paper undertakes validation of monthly TRMM rainfall estimates before using it to understand the spatial and temporal variability in the Basin. This validation based on application of statistical study, made it possible to obtain interesting results with correlation coefficients varying from 0.92 to 0.96 and Nash indices close to 1. The analysis of the seasonal rainfall pattern shows consistence with ground based observations. The study of the annual cycle reveals that their interannual variability is similar to that of ground based observations. Finally, the interpolation of average monthly rainfall in the basin highlights the NorthSouth rainfall gradient, which shows that the South is wetter than the North, with differences more pronounced in August and September.